Quo Vadis: The Welfare State in the Era of Dark Indonesia - Hutauruk, Appe (International Journal Labs, 2025)
In principle, the duty of the state is not only to maintain the order and security of the people but also to strive so that every member of society can enjoy prosperity fairly and equitably. However, in the current political climate of Indonesia, development is primarily oriented toward infrastructure, often neglecting the welfare of the people and marginalizing certain community groups in favor of elite interests. This research employs a normative juridical approach using statutory, conceptual, and case analysis methods to examine the erosion of welfare state principles in Indonesia. The research is grounded in Welfare State Theory, Authority Theory, and Good Governance Theory to critically assess government policies and legal practices. The findings reveal a growing deviation from Pancasila values, with increasing inequality, weakened legal protection, and state alignment with oligarchic interests. These conditions have undermined the core ideals of justice and social welfare. The research concludes that without strong political will, legal reform, and commitment to public accountability, the vision of a welfare state will remain rhetorical. The limitations of this research lie in its reliance on normative analysis without empirical data, suggesting the need for further research incorporating public perspectives and quantitative measurements.